PELEMBAGAAN OPOSISI DALAM SISTEM PRESIDENSIAL: STUDI TENTANG OPOSISI PDIP DI DPR - tuswoyo, tuswoyo (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2013)
In a presidential system of government and opposition relations are not always mutually adversarial, unlike the relationship of government and opposition in countries that adopt a parliamentary system, in a presidential system of government and opposition relations can be negosiable. the mechanism of checks and balances, the opposition parties are able to negotiate, compromise, for the things that are important to the interests of the people. In such a reality, it is not easy to opposition political parties to encourage the process of institutionalization of the opposition in parliament, because the role of the opposition in parliament are not real. Increasing public appreciation theoretically form the capital for the further institutionalization of the opposition, as well as capital for PDIP to win the election. It seems to winning elections is not the case. The decline is one of them triggered by the actions of political elites who run transactional PDIP, which is very disappointing the public.